Improved Laboratory Results for Fixed Restorations Using Sequential Tooth Preparation - David W. Eggleston, DDS (Blackwell Synergy, 2000)
Laboratory reference guides provided by the dentist help ensure optimum results in fixed prosthodontics. A technique is described in which a master cast is made before preparation of the last tooth to be treated. Through this technique, the laboratory prescription includes the dimensions of the new restorations in relation to those of the unprepared tooth replica on the master cast. Thus, the technician is afforded not only a precise guide to restoration contour and size, but also a helpful pretreatment record of the patient’s vertical dimension.